The Developing Students' Attitudes Toward History Through Planning Organizations Strategy - Dr. Hajar Abdel-Dayem Mahdi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Secondary history education often suffers from low student engagement due to passive rote-learning traditional instruction. Specific Background In Iraqi preparatory schools, fourth-grade literary students exhibit declining interest and negative attitudes toward history. Knowledge Gap While graphic organizers are widely recognized in general pedagogy, their specific impact on affective domain dimensions in history learning remains insufficiently evaluated. Aims This study evaluates the effect of an organizational planning strategy on fourth-grade literary female students' attitudes toward history. Results Statistical post-test analysis revealed significant differences favoring the experimental group over the control group. Novelty The research establishes that translating abstract historical concepts into structured visual schematics directly restructures cognitive architecture and elevates affective learning orientation. Implications Integrating structured planning organizers into social studies curricula offers a scalable pedagogical approach to foster sustained academic motivation and dynamic classroom engagement. Keywords: Organizational Planning Strategy, Historical Attitudes, Active Learning, Cognitive Schematics, Secondary Education Key Findings Highlights Implementation of structured visual schematics significantly outperforms traditional lecture methods in improving academic orientation. Active cognitive mapping facilitates meaningful retention by transforming abstract textual facts into organized mental images. Methodological shift from passive reception to learner-centered classification elevates classroom enthusiasm and student engagement.